ANALISIS PERILAKU KONSUMEN TERHADAP NIAT MEMBELI MELALUI SIKAP DAN INTENTION TO ENGAGE PADA MEDIA SOSIAL - Johan Prapta Wijaya; Margaretha Pink Berlianto (Research Center and Case Clearing House PPM School of Management, 2020)
This study aims to investigate the positive effect of perceived usefulness, compatibility, enjoyment, credibility, peer communication on consumer attitudes, the positive effect of consumer attitudes towards consumers' intention to engage, and the positive effect of consumers intention to engage on consumers' intentions to purchase. This study used a quantitative approach, and the samples of this study were gathered from 215 respondents in the Jabodetabek area. This study uses a non-probability sample design, which is purposive sampling with criteria: an individual who is using social media Instagram and follow at least one retail brand Instagram account. The analysis process used is Partial Least Squares-Structural Equation Modeling (PLS-SEM). The results of this study shown that perceived usefulness, compatibility, enjoyment, credibility, peer communication have a positive effect on consumer attitudes, consumer attitudes have a positive effect on consumers' intention to engage, and consumers intention have a positive effect on consumers' intentions to purchase. The study contributes to practitioners regarding influence factors on customer's attitudes toward social media and the effect of customer's attitude on customer engagement toward media social and its impacts on purchase intention.